The nanostructural role of water in lamellar bone and its implications on osteonal bone mechanics: a micrographic and optomechanical study - Utku, Feride Şermin. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2008., 2008)
The microstructural organization of water in bone was investigated using the environmental scanning electron microscope to analyze the dimensional changes that occur during dehydration of equine osteonal bone. In longitudinal sections, 1.2% contraction perpendicular to the lamellae, 0% parallel to the lamellae; in transverse sections,1.4% contraction both parallel and perpendicular to the lamellae were observed. Scanning electron microscopy back scattered electron images showed that about half of an individual lamella is less mineralized, thus more hydrated, indicating that contractions perpendicular to lamellae are due to the presence of more water-filled rather than mineral-filled channels within the mineralized collagen fibril arrays. As these channels are also aligned with the crystal planes, the crystal arrays facilitate or hinder contraction in different directions. The mineralized collagen fibril arrays, laid down in the form of primary circumferential lamellar bone are replaced with secondary osteonal lamellar bone. The mechanical properties of these two types of lamellar bone are studied to understand how bone functions under load during the remodelling process. Twenty minipig cortical bone samples were tested using an optomechanical testing system. Deformation of tissue after each 2-micrometer compression increment was detected orthogonally in-plane (x,y) and out-of-plane (z). Linear regression of stress and strain of partially remodelled bones gave an E1and ν12 of 7.9 ± 2.1 GPa and 0.3. The circumferential lamellar bone had an average E1 of 9.4 ± 2.0 GPa compared to the average E1 of 6.8 ± 0.8 GPa for the osteonal bone.|Keywords: environmental scanning electron microscope, mineralized collagen fibril, bone water, electronic speckle pattern interferometry, mechanical properties of compact bone.
Keywords: Scanning electron microscopy.; Compact bone.; Collagen.